Witch way out - Conte, Cate (New York, NY : Kensington Books, 2023)
While struggling to learn more about her craft and her magickal ancestry, crystal shop owner Violet Mooney must conjure up the clues when her personal hero is murdered during the Spring Equinox Fair, wreaking havoc on both the mortal and magickal worlds.
Keywords: Businesswomen -- Fiction; Witches -- Fiction; Murder -- Investigation -- Fiction; Paranormal fiction; Cozy mysteries; Novels; Mystery fiction